Legality Meets Efficiency: An Integrated Framework for Construction Disputes in National Strategic Projects Evidence From the Ikn Megaproject - Hidayat, Taufik; Asmara, Sukma; Rusliadi, Rusliadi; Novianto, Achmad Mursid (Journal Research of Social Science, Economics, and Management, 2026)
Mega-scale national strategic projects, such as the development of Indonesia’s new capital city (Ibu Kota Nusantara, IKN), situate construction contracts within a highly complex legal environment shaped by multi-party participation, substantial economic value, and heightened public interest considerations. Such complexity increases the risk of construction disputes that may adversely affect not only the contractual relations of the parties but also project continuity and overall legal certainty. This article develops an integrated construction dispute resolution framework that reconciles contractual enforceability and compliance with governing law with procedural efficiency in dispute resolution. Through a doctrinal and conceptual analysis of construction dispute resolution mechanisms—namely litigation, arbitration, and Alternative Dispute Resolution (ADR) processes such as mediation, negotiation, and Dispute Boards—the study demonstrates that embedding ADR mechanisms within well-drafted and enforceable dispute resolution clauses enhances the effectiveness of dispute management without diluting legal certainty. The proposed framework emphasizes the role of tiered dispute resolution clauses and escalation procedures as risk allocation and dispute avoidance tools, operating both preventively and remedially throughout the project life cycle. This study contributes to the refinement of construction contract drafting and dispute system design in national strategic projects and offers normative guidance for policymakers, contract drafters, and construction law practitioners in developing responsive and sustainable dispute resolution regimes.